Can Child Development Accounts be inclusive? Early evidence from a statewide experiment. (June 2015) - Beverly, Sondra G.; Kim, Youngmi; Sherraden, Michael; Nam, Yunju; Clancy, Margaret
Abstract: A key objective of Child Development Accounts (CDAs) is to increase college completion rates among disadvantaged youth by helping families accumulate assets for college and by encouraging youth to see themselves as college bound. While the major asset-building programs in the United States almost exclusively benefit socioeconomically advantaged individuals, CDAs explicitly aim to facilitate account holding and asset accumulation by disadvantaged families. But can CDAs meet the goal of being inclusive? This research uses data from a large CDA experiment with probability sampling and random assignment to examine early savings outcomes. Findings indicate that CDAs improve outcomes for diverse demographic groups and sometimes have greater impacts on disadvantaged children than advantaged children. Features like automatic account opening and automatic initial deposits, which are uncommon in other asset-building programs, extend the opportunities and benefits of asset accumulation to disadvantaged families. Highlights: Child Development Account experiment with probability sampling and random assignment Treatment infants received 529 accounts with 1000. Parents were encouraged to save. Without the CDA, advantaged groups had much more favorable early savings outcomes. With the CDA, there was little or no variation in outcomes by socioeconomic status. Universal and automatic components of the CDA help "level the playing field".